A critical discourse analysis of how public participants and their evidence are presented in health impact assessment reports in Wales. (14th April 2019) - Emmerson, Chris; Wood, Fiona
Abstract: Background: Health impact assessment (HIA) involves assessing in advance how projects affect the health of particular populations. In many countries, HIA has become central to attempts to better integrate health and public participation into policy and decision making. In 2017, HIA gained statutory status in Wales. This study considers how the public and their evidence are presented within HIA reports and what insights this offers into how public participation is constructed within public health. Methods: Critical discourse analysis, as described by Fairclough (2003), to analyse seven HIA reports produced in Wales. Results: Discourses were grouped under four headings. "Consensus and polyphony" relates to the tendency to produce consensus. "Authors and authority" is concerned with how participants and their evidence are shaped by different authorial stances. "Discussions, decisions and planes of action" brings together material on how decision makers are (or are not) brought into contact with evidence in the reports. "Evidence: fragmentation and compression" analyses strategies of abstracting. Conclusions: This analysis suggests that participants and their evidence are presented in specific ways within HIA reports and that these are particularly shaped by genre, authorial stances and approaches to abstracting and re‐ordering texts. Acknowledging these issues may create opportunities to develop HIA in new directions. Further research to test these conclusions and contribute to a wider "sociology of public health documents" would be of value.